2009
DOI: 10.1007/s10815-009-9306-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that human blastomere cleavage is under unique cell cycle control

Abstract: Purpose To understand the molecular pathways that control early human embryo development. Methods Improved methods of linear amplification of mRNAs and whole human genome microarray analyses were utilized to characterize gene expression in normal appearing 8-Cell human embryos, in comparison with published microarrays of human fibroblasts and pluripotent stem cells. Results Many genes involved in circadian rhythm and cell division were over-expressed in the 8-Cells. The cell cycle checkpoints, RB and WEE1, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…Several previous studies have also indicated that cleavage-stage embryos exhibit weakened mitotic checkpoints, potentially facilitating rapid cleavage divisions [25, 26, 27]. These include the G1 and G2 checkpoints [25], corroborated by the finding that transcripts encoding essential checkpoint proteins RB and WEE1 are not detected in 8-cell embryos [26].…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 79%
See 1 more Smart Citation
“…Several previous studies have also indicated that cleavage-stage embryos exhibit weakened mitotic checkpoints, potentially facilitating rapid cleavage divisions [25, 26, 27]. These include the G1 and G2 checkpoints [25], corroborated by the finding that transcripts encoding essential checkpoint proteins RB and WEE1 are not detected in 8-cell embryos [26].…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 79%
“…These include the G1 and G2 checkpoints [25], corroborated by the finding that transcripts encoding essential checkpoint proteins RB and WEE1 are not detected in 8-cell embryos [26]. In mature cells, these checkpoints serve to detect damaged or incompletely replicated DNA, signaling to effector proteins that arrest the cell cycle and initiate apoptosis or DNA repair [28].…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 97%
“…It has been reported that UHRF2 may play important roles in early human development (Kiessling et al, 2009). The overexpression of UHRF2 induces G1 arrest of the HEK293 human embryonic kidney cell line, which indicates that it could behave as an inhibitory factor in cell proliferation (Just, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Clouston et al [2002] reported that the high level of chromosome damage in the form of chromatid breaks and gaps seen in 40% of the blastocysts in that study was suggestive of unrepaired or inappropriately repaired damage in previous division cycles. At the preimplantation stages of development, the cell cycle checkpoints are not fully functional Kiessling et al, 2009], and it could be that the conditions in the culture media where the embryos were kept caused replication stress which then could not be fully repaired, resulting in embryos with a high level of chromosome breaks. Fragouli et al [2008] for instance argue that the relaxation of the G2-M checkpoint during the rapid cell divisions in the blastocyst stage could result in chromosome fragmentation after chromosome lagging on the spindle during cytokinesis.…”
Section: Discussionmentioning
confidence: 99%